EKSPLORASI DAN KONSERVASI EX-SITU PLASMA NUTFAH UBIKAYU SEBAGAI UPAYA MEWUJUDKAN KETAHANAN PANGAN DI MALUKU - La Dahamarudin; Maryam Nurdin (JURNAL AGROTROPIKA, 2009)
Exploration of germplasm cassava is executed in May-June 2007 in SubProvince of Seram Bagian Barat (SBB), Seram Bagian Timur (SBT), and Maluku Tengah. Conservation ex-situ is executed in KP. Makariki. Exploration is executed by using method survey, focused at germplasm collection cassava owned by farmer. From result of exploration, has collected 26 accessions of cassava and conservation in the Station of Germ Plasm Collection, KP. Makariki. Eight accessions i.e., U.KBL, U.SGK, U.ING 1, U.TER, U.JJ, U.GM, U. SM. And U.BPR showed superior characters useful for further cultivar development of cassava. Key words : Exploration and conservation ex-situ, germplasm, cassava.